Performance characteristics of LiMn2O4/polymer/carbon electrochemical cells - Kamarulzaman, N.; Osman, Z.; Muhamad, M.R.; Ibrahim, Z.A.; Arof, Abdul Kariem; Mohamed, N.S. (Elsevier, 2001)
This paper discusses the performance characteristics of two types of cells of configuration LiMn2O4/chitosan/C. LiMn2O4 was prepared by the sol-gel method. The precursor obtained was heated at different temperatures to form LiMn2O4. The performance of the LiMn2O4 compound prepared at different temperatures was investigated by studying the discharge characteristics of the LiMn2O4/LiClO4-EC-DMC/C cells. it was found that the cell utilising LiMn2O4 obtained by heating the precursor at 600 degreesC, for 6 h gave the best performance. The LiMn2O4 compound was then used to fabricate cells using a chitosan-based electrolyte. in one of the cells, the chitosan polymer was doped with 32 salt to represent a salt-in-polymer electrolyte and in the other, the polymer was doped with 75 salt to form a polymer-in-salt electrolyte. The room temperature conductivity for the salt-in-polymer electrolyte was 1.3 x 10(-5) S cm(-1) and that of the polymer-in-salt electrolyte was 3.9 x 10(-3) S cm(-1). The cathode of all cells consists 80 active material 10 binder and 10 carbon by weight, The characteristics of the cells were measured and analysed. (C) 2001 Elsevier Science B.V. All rights reserved.